A general copper-mediated nucleophilic 18F fluorination of arenes - Tredwell, M; Preshlock, S; Taylor, N; Gruber, S; Huiban, M; Passchier, J; Mercier, J; Génicot, C; Gouverneur, V (2014)
Molecules labeled with fluorine-18 are used as radiotracers for positron emission tomography. An important challenge is the labeling of arenes not amenable to aromatic nucleophilic substitution (SNAr) with [ 18F]F-. In the ideal case, the 18F fluorination of these substrates would be performed through reaction of [18F]KF with shelf-stable readily available precursors using a broadly applicable method suitable for automation. Herein, we describe the realization of these requirements with the production of 18F arenes from pinacol-derived aryl boronic esters (arylBPin) upon treatment with [18F]KF/K 222 and [Cu(OTf)2(py)4] (OTf= trifluoromethanesulfonate, py=pyridine). This method tolerates electron-poor and electron-rich arenes and various functional groups, and allows access to 6-[18F]fluoro-L-DOPA, 6-[18F]fluoro-m-tyrosine, and the translocator protein (TSPO) PET ligand [18F]DAA1106. 18F-labeling for PET: The nucleophilic 18F fluorination of pinacol-derived aryl boronic esters is achieved with [18F]KF/K 222 in the presence of [Cu(OTf)2(py)4] (OTf=trifluoromethanesulfonate, py=pyridine); this unprecedented method can produce a clinical dose of 6-[18F]fluoro-L-DOPA in two steps (fluorination followed by deprotection) from a readily available shelf-stable arylBPin precursor (see scheme). RCY=decay-corrected radiochemical yield © 2014 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.